Evaluating the Impact of the Kampus Mengajar Program on Problem-Solving Skills in Primary School Teacher Education Students - Vanesa, Welsa Hira; Putra, M. Jaya Adi; Kurniaman, Otang (AL-ISHLAH: Jurnal Pendidikan, 2024)
Problem-solving is an essential skill for students, necessary for both acquiring knowledge and preparing for future challenges. The Kampus Mengajar Program, part of the MBKM (Independent Learning Independent Campus) initiative by the Directorate General of Higher Education, aims to enhance students’ soft and hard skills, including problem-solving abilities. This study investigates the impact of the Kampus Mengajar Program on the problem-solving skills of Primary School Teacher Education students. This qualitative research focused on students from the Primary School Teacher Education program at Riau University who participated in the Kampus Mengajar Program Batch 3. Data were collected through case studies, with participants' problem-solving abilities being the primary focus. Descriptive analysis was used to present the findings. The findings revealed that the Kampus Mengajar Program had a positive impact on students' problem-solving skills. Through this program, students were able to develop their soft skills, particularly problem-solving, by engaging in real-world teaching experiences and addressing challenges in primary school education. The Kampus Mengajar Program provided a practical platform for students to apply theoretical knowledge in real-world contexts, thereby enhancing their ability to analyze and solve problems. This hands-on experience proved effective in improving the students' problem-solving abilities, making it a valuable component of their teacher education. The Kampus Mengajar Program significantly contributed to the development of problem-solving skills in Primary School Teacher Education students, offering an effective approach to enhance both their soft and hard skills through practical, real-world engagement.